PEMANFAATAN TEKNOLOGI KECERDASAN BUATAN DALAM MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA DI SD - Manihuruk, Waldio; Surya, Edy; Fauzi, Muhammad Amin (Universitas Negeri Medan, 2024)
Students significantly improve their understanding of mathematical topics when they use personalised learning systems powered by artificial intelligence (AI). An effective and tailored learning experience is fostered by AI through its capacity to adjust the learning pace according to each student's degree of comprehension. A survey of AI technology applications is the goal of this research. The limitation in implementing and using AI technology within the framework of mathematics education is the primary challenge that partners are presently encountering. A descriptive analysis based on student surveys is the study approach used. Research objects and related literature are seen, interviewed, and documented as part of the data gathering process. The purpose of doing descriptive analysis on the data acquired is to bolster information that is pertinent, associated, and linked to the research. The study's findings suggest that the following benefits accrue to organisations that are able to make use of AI technology: improved task and role management; enhanced personalised learning and feedback; preparedness to face digital transformation with optimism; and awareness of the significant challenges that lie ahead in the education landscape, particularly in relation to the use of AI in education, including the ethical considerations surrounding its implementation. Keywords: Transformasi Digital, Artificial Intelligences, Mathematics